(untitled) (SAARC Journal of Agriculture, 2019)
Under the changing climate documentation of soil carbon and nutrients is indispensable for sustainable crop production which is scarce in the agro-ecological zone (AEZ) of Northern and Eastern Piedmont Plains in Bangladesh. Therefore, the study was conducted collecting and analyzing a total of 240 soil samples considering 0-20 cm soil depth from two upazilas viz. Purbadhola and Akhaura under the mentioned AEZ to quantity carbon stock and nutrient contents of soils. Organic carbon stocks in soils of Purbadhola and Akhaura upazila were 45.97 and 97.04 Gg, respectively, while in the Northern and Eastern Piedmont Plains was 8.56 Tg. The soil pH was very strongly acidic to slightly acidic (4.4-5.8), organic carbon contents (0.53-1.31%) were very low to medium, while the overall soil fertility rated as very low to medium. Balanced fertilization using organic and inorganic sources in general and liming for upland crops might improve fertility and productive capacity of soils in the study area. The study opens up avenues to find out means and ways of increasing carbon contents in soils of Northern and Eastern Piedmont Plains and might help the policy makers to debate on future global carbon trading issues. SAARC J. Agri., 16(2): 61-72 (2018)